(untitled) (Damascus University Journal for legal sciences, 2024)
A Constitutional Court is deemed to be an independent body vested with various powers enabling it to protect the Constitution and the fundamental citizens’ freedoms and rights by reviewing the constitutionality of legislation in the first place. However, its role cannot be perfectly assumed without having consolidating constitutional and legal structure in terms of rules governing the system of composition and membership, analyzing this structure in several constitutional systems leads us to conclude that the effectiveness of the constitutional judiciary relies essentially on three pillars: the participative character of the appointment process, the prior and decisive fixing of the number of constitutional judges, and the non-renewability of their mandate. Actually, the ways in which the constitutional systems have approached these three pillars are not similar, the different attitudes vis-à-vis the adoption of one or more of these pillars reflect ,in our opinion, the ampleness of the role that the constitution makers wanted to convey to the Constitutional Court. In Syria, these three pillars seem to be not well established, this paper seeks to illustrate the inconveniences that might result from this attitude and it also proposes amendments for both the Constitution of 2012 and the law of the Supreme Constitutional Court so as to enable the consolidation of these three pillars.